2012
DOI: 10.1063/1.4759247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of below-threshold efficiency characteristics of InGaN-based blue laser diodes

Abstract: In this study, we investigate the below-threshold emission characteristics of InGaN-based blue laser diodes (LDs) emitting at 442 nm to study the efficiency droop effects in InGaN LDs. From the measurement of spontaneous emission in the LD, it is observed that the peak efficiency appears at a current density of ∼20 A/cm2 and the efficiency at the threshold current density of ∼2.3 kA/cm2 are reduced to ∼47% of the peak efficiency. The measured spontaneous emission characteristics are analyzed using the carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The Auger recombination coefficient deduced from a fit of the rate equation to the experimental photoluminescence (PL) data in an earlier effort is 1.4-2.0 × 10 −30 cm 6 /s for quasi-bulk InGaN layers [5]; however, the values extracted from EL measurements of LED structures vary by several orders of magnitude among different reports, 10 −32 -10 −24 cm 6 s −1 , the latter group of figures being some 3 orders of magnitude or more higher than the other reported values [1,5,6,[24][25][26][27]. From the analysis of the below-threshold efficiency of blue laser diodes (LDs), Ryu et al [28] have found the Auger recombination coefficient at high carrier densities to be ∼ 3 × 10 −31 cm 6 /s. Note that the direct Auger recombination coefficient decreases exponentially with the bandgap energy if the process involves transitions across the gap [20], which is supported by a fully microscopic many body model [20].…”
Section: Experimentally Determined and Calculated Auger Coefficient Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The Auger recombination coefficient deduced from a fit of the rate equation to the experimental photoluminescence (PL) data in an earlier effort is 1.4-2.0 × 10 −30 cm 6 /s for quasi-bulk InGaN layers [5]; however, the values extracted from EL measurements of LED structures vary by several orders of magnitude among different reports, 10 −32 -10 −24 cm 6 s −1 , the latter group of figures being some 3 orders of magnitude or more higher than the other reported values [1,5,6,[24][25][26][27]. From the analysis of the below-threshold efficiency of blue laser diodes (LDs), Ryu et al [28] have found the Auger recombination coefficient at high carrier densities to be ∼ 3 × 10 −31 cm 6 /s. Note that the direct Auger recombination coefficient decreases exponentially with the bandgap energy if the process involves transitions across the gap [20], which is supported by a fully microscopic many body model [20].…”
Section: Experimentally Determined and Calculated Auger Coefficient Cmentioning
confidence: 99%
“…From the analysis of the below-threshold efficiency of blue laser diodes (LDs), Ryu et al [28] have found the Auger recombination coefficient at high carrier densities to be ∼ 3 × 10 −31 cm 6 /s. Note that the direct Auger recombination coefficient decreases exponentially with the bandgap energy if the process involves transitions across the gap [20], which is supported by a fully microscopic many body model [20].…”
Section: Experimentally Determined and Calculated Auger Coefficient Cmentioning
confidence: 99%
“…[5] Consequently, the threshold current density was reduced from 25 kA cm À2 (13.8 V) [4e] to 3.7 kA cm À2 (9.6 V), [4d] and a continuous-wave lasing was achieved at room temperature. [4d] Compared with the internal quantum efficiency (IQE) of blue LDs (76%) [6] and UV-A LDs (60%), [7] the IQE of UV-C LDs remains very low (2.3%). [3] The insufficient hole injection [8] is responsible for such low IQE, although the DPD technique circumvents the insufficient Mg activation in Al-rich AlGaN by inducing 3D hole gas.…”
Section: Introductionmentioning
confidence: 99%